As-Suyuti's medicine of the Prophet may Allah bless him and grant him peace - As-Suyuti, Jalalu'd-din Abd'ur-Rahman (SAM Pub., 2000)
Written nearly five hundred years ago, this unique work, now translated into easily readable English, gives a clear insight into a perspective of medicine -- and an understanding of what constitutes and causes illness healing -- that have either largely been lost by those who once possessed them, or else not yet discovered by those who have never had access to them.